Team sports and active games to improve speed-strength training of young volleyball players - Lubyshev, E. A.; Titovsky, A. V.; Bodrov, I. M.; Golubnichiy, S. P. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test benefits of an active games prioritizing speed-strength training model for the 10-12 year old volleyball players.